Optimization of Structure and Size for Diaphragm Profile - Cao Angang; Chang Shan; Ding Chunhua; Li Shuo (Jixie chuandong)
Taking the common diaphragm with the conical profile as example,the distribution of stress and security coefficient in profile are analyzed by ANSYS software. According to the analysis results,the original conical line type can be improved and the multi-parameter optimization is carried out by ANSYS OPT module.After optimizing,the stress in profile is reduced and the security is improved.